A note on “anticommons” on aquaculture projects approval - Filipe, José António (2013)
A set of texts on the theory of anti-commons have been published in the last decades concerning the study of property rights. When “anti-commons” emerge resources are prone to be underused because there are too many rights of exclusion. This may be seen in many areas, either social or economic. In Portugal, the processes of aquaculture projects approval depend on too many people (and institutions) decisions. This dependence in the approval process of too many people leads to the sub-utilization of the resources that promoters aim to exploit, because the time used for its approval becomes too long and the project implementation would be too late.